PERAN BIMBINGAN BELAJAR DALAM MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA SD MELALUI METODE BELAJAR SAMBIL BERMAIN (PLAY-BASED LEARNING - Nova Rinda Agustin; Ardani Aurelia Anggita Zahri; Ave Celina Rosita Dewi; Bimo Yudha Wicaksono; Muhammad Altaf Rafikhan; Susi Hermin Rusminati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of tutoring in improving the learning motivation of elementary school students through the application of play-based learning methods. The problem addressed in this study is the low learning motivation of students caused by conventional teaching methods that are uninteresting, rigid, and unsuitable for the learning styles of elementary school-aged children. This study employs a descriptive qualitative approach with data collection techniques including observation, semi-structured interviews, documentation, and literature review. The research was conducted at the NextGen tutoring center located in Driyorejo, Gresik, East Java, with a sample of 8 students, 5 teachers, and 2 parents. The results of the study indicate that the implementation of play-based learning using the digital media Duck Race can create a pleasant learning environment, thereby enhancing students' active engagement, focus, and understanding of science and social studies materials. This study demonstrates that play-based learning is effective in boosting students' learning motivation and can serve as an alternative teaching strategy in both informal and formal education settings.